Challenges to delivering pediatric surgery services in the midst of COVID 19 crisis: experience from a tertiary care hospital of Pakistan - Qazi, Saqib Hamid (Pediatr Surg Int, 2020)
Covid-19 pandemic has significantly challenged the healthcare delivery across the world. Surgery departments across the country responded to this challenge by halting all non-emergency procedures. This delay in diagnosis and management of surgical disease could result in significant mortality and morbidity among the most vulnerable population-the children. In this manuscript, we discuss the measures adopted as well as the challenges faced by the pediatric surgery department at Aga Khan University Hospital, Karachi (AKUH), Pakistan, which is a private, not-for-profit entity and providing optimum surgical care to the patients. We also underscore the need for global strategies for tackling such crisis.